2010
DOI: 10.1007/s00420-010-0547-x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation rate of 6-sulfatoxymelatonin and cognitive performance in offshore fleet shift workers: a field study

Abstract: This field study showed that offshore fleet workers are able to adapt to the imposed regimen of 12-h night shifts. The adaptation is slower compared to other branches of the offshore industry, which most likely is due to lower light exposure. Subjective sleep quality improved to some extent, but the results were not conclusive. No significant effects were observed in the objective measures. Cognitive performance improved significantly, which was likely to be caused by the extended working hours on day 1 and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 49 publications
2
39
0
Order By: Relevance
“…Although the sample size was too small to run reliable statistical analyses for this sub-group, this finding provides further support to the importance of light/darkness exposure for circadian adaptation to night shift work. Spontaneous circadian entrainment to night work has been shown in different populations, including offshore fleet workers [20], oil rig workers [21] and in simulated night shift experiments [19]. The circadian adaptation of these individuals and our police officers was most likely a result of their optimal exposure to environmental synchronizers, such as a favorable light/darkness exposure and the maintenance of a fixed daytime sleep/wake schedule for 7 consecutive days [55].…”
Section: Discussionmentioning
confidence: 88%
“…Although the sample size was too small to run reliable statistical analyses for this sub-group, this finding provides further support to the importance of light/darkness exposure for circadian adaptation to night shift work. Spontaneous circadian entrainment to night work has been shown in different populations, including offshore fleet workers [20], oil rig workers [21] and in simulated night shift experiments [19]. The circadian adaptation of these individuals and our police officers was most likely a result of their optimal exposure to environmental synchronizers, such as a favorable light/darkness exposure and the maintenance of a fixed daytime sleep/wake schedule for 7 consecutive days [55].…”
Section: Discussionmentioning
confidence: 88%
“…Hansen, Geving and Reinertsenʼs field study of offshore vessel workers showed that offshore vessel workers adapted slower to 12-h night shifts compared to their colleagues on oil rigs on similar schedules [46]. This was measured with sulphatoxymelatonin (aMT6s).…”
Section: Discussionmentioning
confidence: 99%
“…This inconsistency can be attributed to environmental conditions such as exposure to light, individual differences (e.g. being morning-oriented), and social/family commitments of the subjects in various studies [1625]. Suppression of melatonin caused by exposure to morning light had been mentioned as a strong factor preventing the adaptation to night work.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Barnes et al, which was conducted on offshore workers involved in two week night shifts and two week day shifts, it was reported that the delay in melatonin occurred during the first week of night work [15]. In addition to shift patterns, adaptation to night work depends on environmental variables such as lighting, individual differences, and seasonal factors [16]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation